0454 Sleep Disruptive Cognitions in Deployment-Related Insomnia. (27th May 2020) - Howell, M; Mellman, T
Abstract: Introduction: Sleep disturbance is common following military deployment, and insomnia is associated with many adverse psychiatric and medical outcomes. Deployment to a threatening environment can engender nocturnal vigilance, which may be a salient feature of sleep disturbance in formerly deployed Veterans. Cognitive behavioral therapy for insomnia (CBTI) is an effective treatment; however, CBTI emphasizes targeting dysfunctional beliefs about sleep (DBAS) and generalized worries rather than vigilance. The goal of the present study was to investigate the role of vigilance, in relation to other potential types of sleep-interfering cognitions in formerly deployed Veterans with sleep disturbance. Methods: Thirty-nine formerly deployed Veterans with disturbed sleep completed measures prior to an intervention. Insomnia was measured with the Insomnia Severity Index (ISI) and measures derived from actigraphy and morning sleep diaries administered for one week. Measures for sleep interfering cognitions included Dysfunctional Beliefs about Sleep (DBAS), the Penn State Worry Questionnaire (PSWQ), a measure of generalized worry, and the Fear of Loss of Vigilance (FLV) subscale of the Fear of Sleep Inventory (FOSI). Results: All of the measures of sleep-interfering cognitions were significantly associated with ISI score. Generalized worries (PSWQ scores) were strongly and significantly correlated with both FLV and DBAS, which were not significantly correlated with each other. FOSI FLV explained 7.1% more variance in ISI score than DBAS alone (p = .04) while DBAS explained 23.1% additional variance in ISI score over FOSI FLV alone (p < .001). Conclusion: It may be important to target both nocturnal vigilance and dysfunctional beliefs about sleep in the treatment of insomnia in formerly deployed Veterans. Support: Supported by W81XWH-14-1-0066 from the Congressionally Directed Peer-Reviewed Medical Research Program of the Department of Defense.